PRINCIPLES OF MODEL CONSTRUCTION OF DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS OF PSYCHOLOGY IN MASTER'S DEGREE - Olha Cherepiekhina (International Journal of Innovative Technologies in Social Science, 2021)
The article reveals the principles of building a model of formation of pedagogical competence in future teachers of psychology in graduate school. In particular, the conceptual block of the model of development of pedagogical competence of future teachers of psychology in the conditions of master's degree defines ideology of the specified development and contains such pedagogical principles: system, continuity, professional orientation, innovation, democratization, electiveness, creativity, professional mobility, problems; unity of scientific, educational and professional activity; informatization; independence, reflectivity.